Zambia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper and Statistical Appendix examines the economic developments in Zambia during the 1990s. Economic activity recovered significantly in 1996. Real GDP expanded by almost 6 1\2 percent, compared with a cumulative decline of 12 1\2 percent in 1994-95. Good rains stimulated agricultural production, while the other nontraditional and mining sectors also contributed to the turnaround in economic activity. However, owing to a sharp deterioration in the terms of trade, largely on account of falling copper prices, real national income increased by only 2 percent.